2018
DOI: 10.1186/s13104-018-3847-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of iodized salt utilization among reproductive women in Addis Ababa City

Abstract: ObjectiveThe objective of this study was to assess knowledge and practice of iodized salt utilization among reproductive women in Addis Ababa city. A cross-sectional study was carried out on 549 households. A sample district was designated by using the simple random sampling techniques. Data were collected by a face-to-face interview and household salt was tested to check whether its practice was good. p < 0.2 in the bivariate logistic regression was entered into the multivariable logistic regression, and p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
40
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 12 publications
12
40
6
Order By: Relevance
“…The odds of iodized salt utilization among households with middle wealth index were higher compared with the poorest once. Our nding is consistent with the nding of many other studies in Ethiopia (19,26,27,29). This might be due to the reason that those households with poorest wealth index are facing economic constraint for buying iodized salt; iodized salt is less likely to be found in poor households due to its relatively higher cost (37).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The odds of iodized salt utilization among households with middle wealth index were higher compared with the poorest once. Our nding is consistent with the nding of many other studies in Ethiopia (19,26,27,29). This might be due to the reason that those households with poorest wealth index are facing economic constraint for buying iodized salt; iodized salt is less likely to be found in poor households due to its relatively higher cost (37).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, those households who were from high community education level had higher chance of iodized salt use compared with households from low community education level. This nding is similar with the result of other pocket studies in Ethiopia (24,(26)(27)(28). This could be due to participants who had education are more likely to be knowledgeable on the use of iodized salt than those who did not have education (26,(34)(35)(36).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Against our expectation, the respondent's knowledge of iodized salt and handling practices had no statistically significant association with the availability of adequate iodine in household salt. A previous similar study in Addis Ababa, however, reported that level of the knowledge does not affect the availability of adequately iodized salt in household salt [20]. We justify our finding by fact that, in the year when this study was conducted, several firms were producing and distributing salt to consumers with unregulated quality [21], and hence access to mixed quality of iodized salt may underestimate the effect of consumer's knowledge about iodized salt and handling practice in maintaining iodine in household salt.…”
Section: Discussionmentioning
confidence: 76%